2014
DOI: 10.1088/0004-637x/794/1/95
|View full text |Cite
|
Sign up to set email alerts
|

A New Method to Obtain the Broad Line Region Size of High Redshift Quasars

Abstract: We present high S/N UV spectra for eight quasars at z ∼ 3 obtained with VLT/FORS. -2 -and metallicity through the use of diagnostic maps built from cloudy simulations. The radius of the broad line region is then derived from the ionizing photon flux applying the definition of the ionization parameter. The r BLR estimate and the width of a virial component isolated in prominent UV lines yields an estimate of black hole mass. We compare our results with previous estimates obtained from the r BLR -luminosity corr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 100 publications
2
23
0
Order By: Relevance
“…We were able to distinguish populations A and B on the basis of the same criteria as were employed at low z applied to the UV (Sect. 2.3 and Negrete et al 2014), and quantitative population A-B differences in EW and profile measurements previously found at low redshift are confirmed in the high-redshift GTC sample. Civλ1549 in population A sources shows a systematically lower EW than population B, as well as blue asymmetric and blueshifted profiles.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…We were able to distinguish populations A and B on the basis of the same criteria as were employed at low z applied to the UV (Sect. 2.3 and Negrete et al 2014), and quantitative population A-B differences in EW and profile measurements previously found at low redshift are confirmed in the high-redshift GTC sample. Civλ1549 in population A sources shows a systematically lower EW than population B, as well as blue asymmetric and blueshifted profiles.…”
Section: Resultssupporting
confidence: 79%
“…The optical and UV (as well as X-ray) criteria are summarized in Sulentic et al (2007). Criteria employed in the present paper are also discussed in Negrete et al (2014) and entail the following: (1) line widths of Aliiiλ1860 and Siiiλ1814 Fig. 3.…”
Section: Observations and Data Reductionmentioning
confidence: 99%
“…More problematic could be the challenge of measuring some of these lines. For example, [Ne iii]λ3343 can potentially be blended with the [Ne v]λ3347 line (Schirmer et al 2013), while Si ii λ1814 has been found to be very weak in high-redshift quasars (Negrete et al 2014). …”
Section: Ne-based Diagnostics In the Near Ultravioletmentioning
confidence: 99%
“…The existence and the brightness of the semi-forbidden emission C III]λ1909 allows to estimate the density as ∼ 10 10 cm −3 (Osterbrock & Ferland 2006). Higher density values are favoured by Moloney & Shull (2014), Negrete et al (2014) and Ruff et al (2012) who fitted the existing hydrogen line intensities with CLOUDY models to reconstruct the spectral shape of the source. They also arrive to a rather large value of ionization parameter U ∼ 0.3.…”
Section: Model Setupmentioning
confidence: 99%
“…In particular, lower-ionization lines like Mg IIλ2800 require systematically lower ionization parameters (and thus larger radii or larger volume and column densities) than higher-ionization lines like C IVλ1549 and He IIλ1640. As it was mentioned in numerous works (Korista & Goad 2000;Negrete et al 2014;Ruff et al 2012;Moloney & Shull 2014), any reasonable fit aiming to reproduce the spectrum of a BLR in details should be multi-component. It is also instructive in more comprehensive models to consider more sophisticated radial distributions of cloud density.…”
Section: Appearance Of the Blrmentioning
confidence: 99%